Tears on the screen: Bodily emotionalism in Reality-Tv - Hirdman,Anja (2011)
Our contemporary culture is in many aspects obsessed with emotions and authenticity. The media figures as a key locus in this development. However, the function and display of emotions vary depending on media type and genre. The article studies the construction of bodily emotionalism in reality-Tv where corporeal signs such as tears confirm the display of emotional authenticity. It argues that authenticity appears to be synonymous with foremost the exposure of so called primary emotions, which are considered expressions for more direct and less controlled impulses. The specific value placed on tears in our culture is discussed in relation to televisions emotional script, the authentic claims of the genre and as a cultural longing after transparency where the ´truth´ resides within the body.